Analisis Determinan Foreign Direct Investment di ASEAN-6 - Inez Angela Eva Maharani; Eni Setyowati (Jurnal Informatika Ekonomi Bisnis, 2024)
FDI is one of the components that can spur economic growth. Developing countries, especially in the ASEAN region, need more capital inflows in the form of foreign direct investment. The purpose of this study is to find out what factors affect FDI in 6 ASEAN countries (Indonesia, Malaysia, Singapore, Thailand, Brunei Darussalam, and Vietnam) for the period 2010-2021. The analysis method used is quantitative analysis method with panel data method approach. Data calculations were carried out using E-views 10 and Microsoft Excel 2019. The variables used are FDI as the dependent variable, while GDP, inflation, interest rates, and trade openness are independent variables. The results showed that the coefficient of determination is 0.7566. That is, 75.66% of FDI is influenced by GDP, inflation, interest rates, and trade openness variables and the rest is influenced by other variables. The estimation results of the F statistical test show the results that GDP, inflation, interest rates, and trade openness together have a simultaneous effect on FDI in 6 ASEAN countries. The t-test found that GDP and trade openness have a partial effect with a positive value on FDI in 6 ASEAN countries. Inflation and interest rates have no partial effect on FDI in 6 ASEAN countries.